Design of Wide-Band Microstrip Antenna for S-Band Telemetry Applications - Pushpalatha M; Namana N; T. S. Navadagi; Varun D (Advanced Electromagnetics, 2023)
This paper exemplifies the design of a low profile wide-band microstrip antenna suitable for S-Band telemetry applications. The proposed design explores the concept of wide-band antenna with improved omnidirectional gain and smaller size essentially aiming at low-earth orbit (LEO) satellite telemetry. The proposed partial annular radiating patch design has an operating impedance bandwidth ranging from 2.7 GHz to 3.8 GHz with a percentage bandwidth of 31%. It exhibits vertical polarization with a gain of around 1.434 dBi. The design and simulations are carried out using 3D EM tools and the measurement results for various performance metrics of the antenna are validated with the simulation results.